Study of plasmon resonance phenomena in metal nanoparticles at low intense excitation - Микитюк, Зіновій Матвійович; Сушинський, Орест Євгенович; Вісьтак, Марія Володимирівна; Петришак, Василь Степанович; Пристай, Тарас Віталійович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper presents the results of experimental and theoretical studies of the synthesized gold nanorods with aiming out their subsequent doping in cholesteric liquid crystals. The synthesis of gold nanorods is done with different aspect ratios and by means of TEM, spectral characteristics and Mie theory, their size is defined. Experimental study of nonlinear parameters of gold nanorods is carried out by means of z-scan technique. In particular, the nonlinear absorption coefficients and refractive indices under the action of laser radiation of low power are calculated. These research results of gold nanorods nonlinearity are a prerequisite for further studies of nonlinear processes of composites based on cholesteric liquid crystals with gold nanorods. According to the research of these composites it is proposed to develop the active materials of primary transducer for harmful substances optical sensors.